2018
DOI: 10.1165/rcmb.2017-0040oc
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA Dysregulation in Pulmonary Arteries from Chronic Obstructive Pulmonary Disease. Relationships with Vascular Remodeling

Abstract: Pulmonary vascular remodeling is an angiogenic-related process involving changes in smooth muscle cell (SMC) homeostasis, which is frequently observed in chronic obstructive pulmonary disease (COPD). MicroRNAs (miRNAs) are small, noncoding RNAs that regulate mRNA expression levels of many genes, leading to the manifestation of cell identity and specific cellular phenotypes. Here, we evaluate the miRNA expression profiles of pulmonary arteries (PAs) of patients with COPD and its relationship with the regulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 52 publications
1
30
0
Order By: Relevance
“…Thereby, gastrodin has been considered as a potential therapeutic agent for diverse diseases such as Tourette syndrome, 7 myocardial infarction, 8 alcoholic liver disease 6,9 and acute lung injury. [11][12][13] For instance, in vivo and in vitro data demonstrated that miR-3202 could protect smokers from COPD. microRNAs (miRNAs) are a sort of small non-coding RNAs that are latterly discovered.…”
mentioning
confidence: 99%
“…Thereby, gastrodin has been considered as a potential therapeutic agent for diverse diseases such as Tourette syndrome, 7 myocardial infarction, 8 alcoholic liver disease 6,9 and acute lung injury. [11][12][13] For instance, in vivo and in vitro data demonstrated that miR-3202 could protect smokers from COPD. microRNAs (miRNAs) are a sort of small non-coding RNAs that are latterly discovered.…”
mentioning
confidence: 99%
“…E2F1, a key proliferative factor, 29 , 30 was found to be targeted by miR-197 and participate in the vascular remodeling of COPD. 12 In fact, despite of ZFP161 and SP4, the remaining transcription factors have been reported in COPD, 31 – 33 which in turn supports the importance of these candidate DEMs in the pathogenesis of COPD.…”
Section: Discussionmentioning
confidence: 85%
“…NGF has also been implicated in viral respiratory infections, either by enhancing viral entry into the cell or airway inflammation (50,51) .Since nicotine stimulated expression of NGF , we then focused on determining whether miR-98 regulated NGF expression (21). miR-98 upregulation has been associated with vascular remodeling in smokers and patients with COPD (52). Decreased miR-98 levels have been associated with the development of pulmonary fibrosis in a model of bleomycininduced lung injury (53).…”
Section: Discussionmentioning
confidence: 99%